High salivary soluble L-selectin and interleukin-7 levels in Asian Indian patients with primary Sjögren's syndrome. Issue 12 (December 2016) - Kabeerdoss, Jayakanthan; Sandhya, Pulukool; Mandal, Santosh; Gowri, Mahasampath; Danda, Debashish
Abstract In present study, we aimed to study salivary soluble L-selectin (sL-selectin), interleukin-7(IjL-7), and lymphotoxin-α levels in primary Sjögren's syndrome (pSS) and their clinical as well as serological correlations. pSS patients fulfilling either the American European Consensus Group (AECG) and/or the American college of Rheumatology (ACR) criteria were recruited. Age- and sex-matched hospital staff were recruited as healthy controls. Unstimulated saliva was collected by the spitting method; sL-selectin, IL-7, and lymphotoxin-α were measured in the saliva using commercial ELISA kits. Forty-three patients with pSS and 31 healthy controls were included in the study. Increased levels of sL-selectin and IL-7 were found in the saliva of patients as compared to controls. Lymphotoxin-α was undetectable in the saliva of pSS patients and controls. Salivary sL-selectin positively correlated with rheumatoid factor (r = 0.47;p < 0.003). No other variable including ESSDAI was significantly associated with salivary sL-selectin and IL-7 levels. Indian patients with primary Sjögren's syndrome have higher salivary sL-selectin and IL-7 levels than healthy controls.